Cross-species analysis of viral nucleic acid interacting proteins identifies TAOKs as innate immune regulators - Pennemann, Friederike L.; Mussabekova, Assel; Urban, Christian; Stukalov, Alexey; Andersen, Line Lykke; Grass, Vincent; Lavacca, Teresa Maria; Holze, Cathleen; Oubraham, Lila; Benamrouche, Yasmine; Girardi, Enrico; Boulos, Rasha E.; et al. (Nature communications, 2021)
The cell intrinsic antiviral response of multicellular organisms developed over millions of years and critically relies on the ability to sense and eliminate viral nucleic acids. Here we use an affinity proteomics approach in evolutionary distant species (human, mouse and fly) to identify proteins that are conserved in their ability to associate with diverse viral nucleic acids. This approach shows a core of orthologous proteins targeting viral genetic material and species-specific interactions. Functional characterization of the influence of 181 candidates on replication of 6 distinct viruses in human cells and flies identifies 128 nucleic acid binding proteins with an impact on virus growth. We identify the family of TAO kinases (TAOK1, −2 and −3) as dsRNA-interacting antiviral proteins and show their requirement for type-I interferon induction. Depletion of TAO kinases in mammals or flies leads to an impaired response to virus infection characterized by a reduced induction of interferon stimulated genes in mammals and impaired expression of srg1 and diedel in flies. Overall, our study shows a larger set of proteins able to mediate the interaction between viral genetic material and host factors than anticipated so far, attesting to the ancestral roots of innate immunity and to the lineage-specific pressures exerted by viruses. Whether there are conserved nucleic acid (NA) binding proteins across species is not fully known. Using data from human, mouse and fly, the authors identify common binders, implicate TAOKs and show that these kinases bind NAs across species and promote virus defence in mammalian cells.